Study on the Wearability Test Bed for the Oversized Chain - Shi Jingbi; Wang Shungong; Zhao Youkun; Wang Kui; Liu Yi (Jixie chuandong)
The power curves of the oversized chains over 56B are deficiency in the ISO or GB standard. All the parameters of the oversized chains remain to be tested. A test machine based on the principle of closed power flow is developed for the oversized chains testing. The basic composition，technical parameters and testing range are introduced. The characteristics of the oversized chains under the condition of pressure spray oil lubrication over 56B，such as wearability，power capacity and other characteristics of running in different speed and load can be tested，the technical data for the chains developers is provided.